The Relationship Between Stress And Adolescent Academic Perception Ability Based On Gender And Body Mass Index - Alfiandari, A. Dhini; Ichsan, Rayhani; Aminuddin, Nurul Mutiah; Damry , Nurul Muf’idah (Al Makki Publisher, 2025)
Stress in adolescents has the potential to impact various aspects of physical and mental health, including perceived academic ability. Differences in gender and nutritional status such as body mass index (BMI) can affect stress levels and academic perception abilities in adolescents. Objective: To assess the relationship between stress and academic perception abilities based on gender and BMI in high school-aged adolescents. Methods: An observational analytical study with a cross-sectional approach was conducted on 53 students aged ≤18 years at SMAN 2 Parepare. Data were collected through an online questionnaire using the Indonesian version of the PSS-10 instrument and the TASES scale. BMI was calculated from weight and height. Data were analyzed using the t-test, ANOVA, and Pearson correlation. Results: There were no significant differences in stress scores or academic perception abilities based on gender and BMI category (p>0.05). There was no significant relationship between stress and academic perception abilities (r=–0.02; p=0.901). Conclusion: Gender and BMI status do not significantly influence stress and academic perception abilities. Other factors such as coping strategies and social support need further investigation.